Key drivers of ozone change and its radiative forcing over the 21st century - F. Iglesias-Suarez (Atmospheric Chemistry and Physics, 2018)
Over the 21st century changes in both tropospheric and stratospheric ozone are likely to have important consequences for the Earth's radiative balance. In this study, we investigate the radiative forcing from future ozone changes using the Community Earth System Model (CESM1), with the Whole Atmosphere Community Climate Model (WACCM), and including fully coupled radiation and chemistry schemes. Using year 2100 conditions from the Representative Concentration Pathway 8.5 (RCP8.5) scenario, we quantify the individual contributions to ozone radiative forcing of (1) climate change, (2) reduced concentrations of ozone depleting substances (ODSs), and (3) methane increases. We calculate future ozone radiative forcings and their standard error (SE; associated with inter-annual variability of ozone) relative to year 2000 of (1) 33 ± 104 m Wm−2, (2) 163 ± 109 m Wm−2, and (3) 238 ± 113 m Wm−2 due to climate change, ODSs, and methane, respectively. Our best estimate of net ozone forcing in this set of simulations is 430 ± 130 m Wm−2 relative to year 2000 and 760 ± 230 m Wm−2 relative to year 1750, with the 95 % confidence interval given by ±30 %. We find that the overall long-term tropospheric ozone forcing from methane chemistry–climate feedbacks related to OH and methane lifetime is relatively small (46 m Wm−2). Ozone radiative forcing associated with climate change and stratospheric ozone recovery are robust with regard to background climate conditions, even though the ozone response is sensitive to both changes in atmospheric composition and climate. Changes in stratospheric-produced ozone account for  ∼  50 % of the overall radiative forcing for the 2000–2100 period in this set of simulations, highlighting the key role of the stratosphere in determining future ozone radiative forcing.